The Morphology of Nineteenth-Century Cities in the United States - Conzen, Michael (Urban History Review / Revue d'histoire urbaine, 1980)
Set within the context of varying traditions of Western urbanism, the U.S. city is considered as a partially autonomous creation, and emphasis is placed on the development of its physical forms during the crucial period of the nineteenth century. Nine distinguishing morphological characteristics such as low density, indistinct urban fringes, and short life of buildings are given special stress. Five broad themes, ranging from the nature of the American environment to the cultural value of land and government, are suggested as possible explanations of American physical urban traits. This is followed by a review of concepts and general findings regarding the three basic components of American urban form: land use ecology, history of building fabric, and cadastral patterns. The essay closes with a more detailed analysis of trends in the last category, given the dearth of conceptual clarity concerning this component. General changes in and representative examples of simple and complex urban ground plans of U.S. cities in the nineteenth century include colonial antecedents, new town foundations, and mature town accretions and modifications both on urban fringes and within densely-built urban cores. Finally, a preliminary division of the century into three morphogenetic periods is offered with a view to stimulating further development of the suggested framework.